1997
DOI: 10.1097/00007632-199712010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cells in Experimental Intervertebral Disc Injury

Abstract: The results suggest the presence of only modest inflammatory cell infiltration in experimental intervertebral disc injury at all follow-up times. The inflammatory response in partial-thickness anterior experimental intervertebral disc injury, in the absence of disc prolapse, seems to be dominated by a T lymphocyte response. The macrophage response is apparently strongest at 1 month after such injury. These findings differ from what has been observed in herniated disc tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…Different animal models of the annular defect have shown that the healing is defective and probably initiates degeneration of the disc. [29][30][31][32] The tears demonstrated at the periphery of the annulus fibrosus may play a critical role in discogenic low back pain and the initiation of degenerative changes. The formation of vascularised granulation tissue may be a physiological response to repair the injury to the annulus.…”
Section: Discussionmentioning
confidence: 99%
“…Different animal models of the annular defect have shown that the healing is defective and probably initiates degeneration of the disc. [29][30][31][32] The tears demonstrated at the periphery of the annulus fibrosus may play a critical role in discogenic low back pain and the initiation of degenerative changes. The formation of vascularised granulation tissue may be a physiological response to repair the injury to the annulus.…”
Section: Discussionmentioning
confidence: 99%
“…Disc tissue, especially NP, has been reported to possess inflammatory properties [7,4], and can secrete cytokines [14] that are closely related to the metabolism of osteoblast [17]. Furthermore, exposure of NP, which is normally excluded from circulation, to the fusion environment may also cause some immune reactions [4,7,13]. Our previous in vitro study showed that disc tissue could influence the metabolism of osteoblastlike cells [9].…”
Section: Haisheng LI Xuenong Zou Malene Laursen Niels Egund Martin Limentioning
confidence: 99%
“…Although mechanical nerve root compression may contribute to the symptoms of radiculopathy, it is currently believed that an inflammatory or immune component is the key mediator of radicular pain (1,2). The nucleus pulposus (NP) tissue may be autoantigenic; this theory is supported by the accumulation of lymphocytes in regional lymph nodes following exposure to autologous NP (3) and injury to the annulus fibrosus (4). A number of animal studies applied healthy autologous NP to spinal nerve roots, as a model of non-compressive disc herniation, which induced an inflammatory and immune response resulting in neuronoglial apoptosis, a decrease in nerve conduction velocity, the onset of gait abnormality, mechanical allodynia and thermal hyperalgesia (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%